Hi-de-ho : the life of Cab Calloway - Shipton, Alyn (Oxford University Press, 2010)
Clad in white tie and tails, dancing and scatting his way through the "Hi-de-ho" chorus of "Minnie the Moocher," Cab Calloway exuded a sly charm and sophistication that endeared him to legions of fans. In Hi-de-ho, author Alyn Shipton offers the first full-length biography of Cab Calloway, whose vocal theatrics and flamboyant stage presence made him one of the highest-earning African American bandleaders. Shipton sheds new light on Calloway's life and career, explaining how he traversed racial and social boundaries to become one of the country's most beloved entertainers. D